On the reliability of motor evoked potentials in hand muscles of healthy adults: a systematic review - Osnabruegge, Mirja; Kanig, Carolina; Schwitzgebel, Florian; Litschel, Karsten; Seiberl, Wolfgang; Mack, Wolfgang; Schecklmann, Martin; Schoisswohl, Stefan (Frontiers in Human Neuroscience, 2023)
Motor evoked potentials (MEP) elicited by transcranial magnetic stimulation (TMS) over the primary motor cortex are used as a neurophysiological marker of cortical excitability in clinical and scientific practice. Though, the reliability of this outcome parameter has not been clarified. Using a systematic approach, this work reviews and critically appraises studies on the reliability of MEP outcome parameters derived from hand muscles of healthy subjects and gives a proposal for most reliable TMS practice. A systematic literature research was performed in PubMed, according to the PRISMA guidelines. Articles published up to March 2023 that were written in English, conducted repeated measurements from hand muscles of healthy subjects and reliability analysis were included. The risk of publication bias was determined. Two authors conducted the literature search and rated the articles in terms of eligibility and methodical methodological criteria with standardized instruments. Frequencies of the checklist criteria were calculated and inter-rater reliability of the rating procedure was determined. Reliability and stimulation parameters were extracted and summarized in a structured way to conclude best-practice recommendation for reliable measurements. 28 articles were included in the systematic review. Critical appraisal of the studies revealed methodological heterogeneity and partly contradictory results regarding the reliability of outcome parameters. Inter-rater reliability of the rating procedure was almost perfect nor was there indication of publication bias. Identified studies were grouped based on the parameter investigated: number of applied stimuli, stimulation intensity, reliability of input-output curve parameters, target muscle or hemisphere, inter-trial interval, coil type or navigation and waveform. The methodology of studies on TMS is still subject to heterogeneity, which could contribute to the partly contradictory results. According to the current knowledge, reliability of the outcome parameters can be increased by adjusting the experimental setup. Reliability of single pulse MEP measurement could be optimized by using (1) at least five stimuli per session, (2) a minimum of 110% resting motor threshold as stimulation intensity, (3) a minimum of four seconds inter-trial interval and increasing the interval up to 20 s, (4) a figure-of-eight coil and (5) a monophasic waveform. MEPs can be reliably operationalized.